Dampak Media Sosial terhadap Pemahaman Ajaran Buddha : Studi pada Mahasiswa STABN Raden Wijaya - Sutta Anuyoga Pratama (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
In this increasingly advanced digital era, social media has become an integral part of the lives of young people, including university students. Social media is not only used for communication and entertainment but is also being utilized as a learning tool, including in a religious context. This study aims to explore the impact of social media use on the understanding of Buddhist teachings among students at the Raden Wijaya State Buddhist College (STABN). The approach used was quantitative, employing a survey method involving students who actively use social media. The main theories employed are Uses and Gratifications, which emphasizes that media users actively choose media to fulfill specific needs, and the theory of social media construction, which views reality as being shaped through digital interactions. This study found that the intensity and habit of social media use are related to the level of understanding of Buddhist teachings. Students who more frequently use social media to seek religious information tend to demonstrate a better understanding of Dhamma values. However, the type of religious content consumed does not always have a direct impact on deeper understanding. These results indicate that social media has the potential to be a positive tool for religious education if used wisely.